From suffering to resignation: Grounded Theory approach to maternal experience with newborn in phototherapy - Tayomara Ferreira Nascimento; Marla Andréia Garcia de Avila; Silvia Cristina Mangini Bocchi
Abstract Objectives: understanding the experience of puerperal womenwith newborn in phototherapy treatment in rooming-in care. Methods: qualitative research analyzed according to the Grounded Theory and the results discussed in the light of Symbolic Interactionism. The interviews were audiotaped and transcribed in full. The theoretical saturation was based on the analysis of the 15th interview with puerperal women, undergoing the experience in the maternity of the Public Hospital of São Paulo State. Results: from the analysis emerged four categories (sub processes): getting disappointed with the bad news; feeling recluse, separated from her baby, accountable and with not enough support for care; resigning to the protective role of mother of a baby in suffering and at risk; seeking strategies to deal with the situation. From the realignment of these categories (sub processes) emerged the core category (process): from suffering to resignation in order to deal with the maternal experience with NB in phototherapy. Conclusions: the symbolic intervening component, mother's protective role, prompted her to attempt to cope with the challenging experience by feeling compelled to exercise the function of caretaker. The same way that the rooming-in care team emerged in the experience of the mother, using the same symbol, to hold her accountable for constant vigilance in maintaining the integrity of baby's vision.